La abstracción en Tomás de Aquino: una vía más allá de la epistemología tomista - Cuccia, Emiliano (2018)
“Abstraction in Thomas Aquinas: Beyond Thomistic Epistemology”. This paper aims to justify the importance of a renewed way to analyze the doctrine of abstraction in Thomas Aquinas, considering that different studies so far a) show difficulties to correctly interpret some key texts of the Angelic, and b) have spawned debates and disagreements among scholars to the point of preventing the development of a common doctrine on the subject. Throughout the paper, two texts will be analyzed in order to show the contrast between what is said and what has been commonly interpreted from them.